A STUDY ON THE EFFECT OF CYCLIC THERMAL OXIDATION AND HEAT TREATMENT ON CERAMIC-REINFORCED METAL COMPOSITE COATING WC12CO â NICRALY USING HVOF THERMAL SPRAY METHOD - Dafa Arkaan, Muhammad
Surface degradation is a major problem that occurs in various engineering components that are applied to aggressive environments and operate at high temperatures. Under these environmental conditions, components often fail due to oxidation caused by cyclic thermal operating conditions. One way that can be done is to improve the surface properties of the material by coating the surface. In this research, coating using ceramic-reinforced metal composite powder WC – Co/NiCrAlY on SS 316 substrate with HVOF thermal spray method. Several tests and treatments were carried out on the coating such as thermal cyclic oxidation test, hardness testing, SEM – EDS Mapping, XRD, and heat treatment. The results of the thermal cyclic oxidation test show that the oxidation rate of the coating has the highest value at the beginning of the cycle and then the oxidation rate decreases in the middle of the test cycle and is relatively stable until the end of the test cycle, which is perhaps coating enters the passivation region. In addition, the layer hardness increased after thermal cyclic testing and after heat treatment. From the results of the research conducted, it shows that the coating is good enough to be used on components that operate at high temperatures such as boiler tubes.